A rare variation of the inferior mesenteric vein with clinical implications. Issue 1 (2019) - Park, Danielle; Blizard, Sarah; O'Toole, Natalie; Norooz, Sheeva; Torre, Martin Dela; Son, Young; McGuinness, Michael; Xu, Mei
No abstract available